2017
DOI: 10.1016/j.heliyon.2017.e00330
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of agro waste pectin for the production of industrially important polygalacturonase

Abstract: In the present study, a variety of agro-industrial wastes have been utilized for meaningful purpose to produce valuable biocatalyst. All wastes used were low cost and easily accessible while, some available throughout the year. A number of bacterial strains isolated from rotten fruits and vegetables were screened for the production of industrially important polygalacturonase (PGase) using pectin present in these agro-industrial wastes. The strain producing maximum PGase was identified as Bacillus licheniformis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Several agro-industrial waste like wheat bran, rice bran can be effective for production of industrially important enzymes [11]. According to Jahan et al, 2017 [12] wheat bran was found to be the best source production of pectinases. Ten days of incubation period was optimal to yield high enzyme titres (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Several agro-industrial waste like wheat bran, rice bran can be effective for production of industrially important enzymes [11]. According to Jahan et al, 2017 [12] wheat bran was found to be the best source production of pectinases. Ten days of incubation period was optimal to yield high enzyme titres (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…All were incubated in an incubator at 37 ± 2 °C for 24, 48 and 72 h in static condition. After, the respective fermentation period, the pectinase and amylase activity was determined to find the optimum fermentation period …”
Section: Methodsmentioning
confidence: 99%
“…Employment of agro‐residues as an alternative carbon source in lieu of commercial xylan or pectin substrates, ensures an economically affordable manufacturing of xylanase and pectinase enzymes . Among various agro‐industrial residues, wheat bran has been mainly reported as a suitable carbon source for the production of xylanase and pectinase enzymes . This study encompasses the enhancement in the yield of xylanase and pectinase enzymes from Bacillus pumilus AJK strain along with reduction in fermentation time interval, using the polysaccharides extracted from wheat bran and citrus peel agro‐waste residues.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Among various agro-industrial residues, wheat bran has been mainly reported as a suitable carbon source for the production of xylanase and pectinase enzymes. 13,[25][26][27][28][29][30] This study encompasses the enhancement in the yield of xylanase and pectinase enzymes from Bacillus pumilus AJK strain along with reduction in fermentation time interval, using the polysaccharides extracted from wheat bran and citrus peel agro-waste residues. Two-stage statistical design approach was adopted for optimizing solid substrate fermentation process parameters.…”
Section: Introductionmentioning
confidence: 99%